A Randomized, Vehicle-Controlled Phase 3 Study of Aminolevulinic Acid Photodynamic Therapy for the Treatment of Actinic Keratoses on the Upper Extremities. Issue 7 (July 2019) - Brian Jiang, Shang I.; Kempers, Steven; Rich, Phoebe; Marcus, Stuart; Houlihan, Anna; Piacquadio, Daniel; Pariser, David
Abstract : BACKGROUND: Blue-light aminolevulinic acid photodynamic therapy (ALA-PDT) after broad-area application and 3-hour incubation is efficacious for actinic keratosis (AK) lesion clearance on upper extremities, with use of occlusive dressing significantly increasing efficacy. OBJECTIVE: To prove the safety and efficacy of ALA-PDT versus vehicle (VEH-PDT) in the spot treatment of multiple AKs on upper extremities. METHODS: Aminolevulinic acid or VEH was spot applied only to lesions on one upper extremity 3 hours before blue-light exposure. Treated extremity was covered with occlusive dressing during incubation. Identical treatment was repeated at Week 8 if AK lesions were present in the treated area. RESULTS: Thirty-one percent (42/135) of subjects treated with ALA-PDT had complete clearance at Week 12, compared with 13% (17/134) of the subjects treated with VEH-PDT ( p = .0001). The mean AK lesion clearance rate for ALA-treated subjects at Weeks 8 and 12 was 53% and 69%, respectively, compared with 26% and 30% for the VEH-treated group ( p < .0001, linear mixed model). Safety profile observed in this study is consistent with previous studies/reports in the literature, and the therapy was well tolerated overall. CONCLUSION: Aminolevulinic acid-PDT spot treatment using a 3-hour occluded incubation was superior to VEH-PDT for AK lesion clearance of the upper extremity.